Role of Civil Society in Strengthening Democratic Governance in India - Sathish Kumar A.S.; Amrutha G.D., (ಅಕ್ಷರಸೂರ್ಯ (AKSHARASURYA), 2026)
Civil society occupies a pivotal position in the functioning and consolidation of democratic governance, particularly in plural and developing democracies such as India. Acting as an intermediary between the state and citizens, civil society organizations (CSOs) contribute to democratic deepening by enhancing political participation, ensuring accountability, protecting rights, and promoting social inclusion. In India, civil society has historically played a transformative role-from the nationalist movement to contemporary struggles for transparency, environmental justice, gender equality, and social welfare. This paper examines the role of civil society in strengthening democratic governance in India by analyzing its conceptual foundations, historical evolution, functional contributions, and emerging challenges. It argues that civil society strengthens democratic governance through advocacy, participatory engagement, policy monitoring, and capacity building at the grassroots level. However, the paper also highlights constraints such as regulatory restrictions, shrinking civic space, politicization, and issues of representativeness and accountability within civil society itself. Using a qualitative and analytical approach, supported by secondary sources, the study underscores the need for a collaborative, transparent, and enabling environment to ensure that civil society continues to act as a vital pillar of India’s democratic governance framework.
Keywords: Civil Society; Democratic Governance; Participation; Accountability; India